Organizing knowledge in libraries : an introduction to information retrieval - Needham, Christopher Donald (London : Deutsch, 1971)
This book contains the present need for an up to date elementary textbook on classification and cataloguing.
Includes index
Includes bibliographical references
aia 14/06/17
Loans
Keywords: Cataloging; Classification--Books